From smart specialisation to smart specialisation policy. Issue 4 (7th October 2014) - Foray, Dominique
Abstract : Purpose: – The purpose of this paper is to focus on the distinction between smart specialisation and smart specialisation policy and it studies under what conditions a smart specialisation policy is necessary. Design/methodology/approach: – A conceptual framework is built based on historical evidence of successful dynamics of structural changes at regional level qualified as "smart specialisation". The identification of market and coordination failures that are likely to impede the occurrence of spontaneous process of smart specialisation makes a good case for a smart specialisation policy. Findings: – The paper highlights important design principles for the policy process that should help to minimise potential risks of policy failures and policy capture. Research limitations/implications: – The paper does assess the effect of smart specialisation on innovation and growth at regional level because it is too early to observe and measure effects. The paper confines itself to conjectures about the effects of such a policy. Practical implications: – The paper makes recommendations and explains some of the practicalities about the implementation of the policy at regional level. Originality/value: – The paper is one of the first dealing with the topic of smart specialisation policy.